Biodiversity and sectoral responsibility in Swedish forestry policy 1988-1993 : "Mellan samhället och den enskilde" - Bush, Terrence (SLU/Southern Swedish Forest Research Centre, 2005)
In 1993 the Swedish parliament substantially revised the nations Forestry Act, deregulating forestry operations and establishing an environmental goal for national forestry policy equal to the previous goal of high production. long the leading aim for Swedish forestry These actions resulted from an extended process during late 1980s and early 1990s, trough which Swedish forestry developed its sectoral responsibilities for nature conservation measures, in particular the protection of biological diversity within the context of timber and pulp production. This thesis examines the legislative history behind these changes, including the ideas and concepts drawn from comprehensive environmental legislation approved during the same period. another legacy of the period is the inclusion of specific legal protection for small forest and agricultural habitats in the Nature Conservancy Act. This paper also explores the impact of this measure on Swedish forestry, specifically the efforts of the national forestry agency to retain authority to administer the habitat protection law on forestland, the majority of Sweden's land cover.